The Effect Of Liquidity, Leverage, And Size Of The Audit Committee On Financial Distress (Empire Study On Property And Real Estate Manufacturing Companiese Listed On The Indonesia Stock Exchange For During The 2018-2020 Period) - Alethea Delfina (Fakultas Bisnis, 2022)
The research purposed to assesed wheter Liquidity, Leverage, and Size of the Audit Committee partially or simultaneously affect Financial Distress. The object used is a property and real estate sub-sector manufacturing company listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The quantitative research used with the descriptive statistical test, classical assumption test, coefficient of determination test, multiple linear regression analysis, and hypothesis testing and the population used are property and real estate companies. All tests will be processed using SPSS software version 25. The sampling technique was purposive sampling, there are 38 companies from 79 property and real estate manufacturing companies. So, there are 114 data samples that will be used. The result showed that liquidity, leverage, and size of the audit committee influence financial distress either partially or simultaneously. Liquidity positively affect the financial distress. Meanwhile, leverage and size of the audit committee negatively affect the financial distress.